FAKTOR – FAKTOR YANG MEMENGARUHI MASALAH MENTAL EMOSIONAL REMAJA DI SEKOLAH MENENGAH KEJURUAN (SMK) SWASTA SE KOTA PADANG PANJANG TAHUN 2018 - Ainil Fitri; Meri Neherta; Heppy Sasmita (Jurnal Keperawatan Abdurrab, 2019)
Adolescent's uncontrolled mental and emotional conditions can affect adolescent behavior and cause problems in the teen's mental and emotional health. This study aims to find out what are the factors that influence the mental emotional problems of adolescents. The study was conducted in Private Vocational Schools (SMK) throughout the city of Padang Panjang in 2018. The research design was descriptive. The sample amounted to 124 adolescents, with a total sampling technique after screening. The instruments used in this study were the SDQ (Strengths and Difficulties Questionnaire) questionnaire and questionnaires factors that influenced adolescent mental emotional problems. The results of this study indicate that, parenting factors are one of the factors that influence the mental emotional problems of adolescents. Most of the parenting styles applied by the respondents' parents were authoritarian and permissive parenting ie 58.4%. Both of these parenting styles have an impact on adolescent mental emotional problems, which are on average in the category of risk (risk). Suggestions from this research are expected to soul nurses in the community so that more often establish communication with the school and hold parenting activities in order to create emotional and mental health conditions especially at school.